Effect of starch-coated magnetic particles on treatment performance and membrane fouling in membrane bioreactor for low carbon/nitrogen municipal wastewater treatment. Issue 2 (April 2023) - Hong, Q.K.; Wang, K.M.; Wu, C.H.; Qiu, Z.X.; Shen, Y.X.; Zhou, J.H.; Wang, H.Y.
Abstract: Membrane bioreactor (MBR) is an attractive sewage treatment technology but the major weakness remains in membrane fouling. Nowadays, magnetic activated sludge process with magnetic particle addition has been extensively investigated for membrane fouling mitigation due to the excellent magnetic bio-effect. However, the bioeffect is still limited and further study to enhance the fouling control is needed. Herein, the starch-coated magnetic particles (Ms P) were fabricated and utilized to alleviate membrane fouling and enhance the treatment performance for low carbon/nitrogen municipal wastewater treatment. The Ms P addition in MBR can effectively mitigate the membrane fouling which might be due to the magnetic bio-effect and enhanced bioflocculation, leading to the lower soluble microbial product (SMP) concentration from 17.3 ± 1.7 to 13.1 ± 0.7 mg L −1, higher microbial dehydrogenase activity from 234.65 ± 11.21 to 430.57 ± 39.48 mgTF gVSS −1 h −1, bigger sludge particle size and more extracted extracellular polymer substances (EPS) secretion in the bulk sludge. Additionally, Ms P particle can facilitate to form an aerobic and anoxic microenvironment, which is conducive to improve the nitrogen removal for low carbon/nitrogen municipal wastewater treatment. Microbial diversity analyses revealed that Ms P addition enriched Flavobacterium sp, leading to more EPS secretion and therefore enhance the hydrophobic property and aggregation ability of sludge flocs to mitigate membrane fouling. Rhodobacter sp was also accumulated, indicating better denitrification process for total nitrogen removal. This study provided evidence for the efficiency of adding Ms P to MBR in order to suppress membrane fouling and improve nitrogen removal for low carbon/nitrogen municipal wastewater treatment. Graphical Abstract: ga1 Highlights: Ms P addition in MBR can further mitigate the membrane fouling compared with MP. Higher TN removal efficiency was obtained for low C/N wastewater with Ms P addition. Ms P addition can enhance bioflocculation and form an aerobic-anoxic micro-environment. The bulk sludge was changed due to magnetic bio-effect and enhanced bioflocculation. Flavobacterium and Rhodobacter were accumulated with Ms P addition.